2011
DOI: 10.1016/j.ejpain.2010.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Parental catastrophizing about their child's chronic pain: Are mothers and fathers different?

Abstract: Preliminary evidence suggests that parental catastrophizing about their child's pain may be important in understanding both parental responses to their child's pain and the child's pain experience. However, little is known about potential differences between mothers and fathers. There were three aims of the present study addressing this lack of knowledge: i) to investigate the three-factor structure of the German version of the Parental Pain Catastrophizing Scale (PCS-P) (Goubert et al., 2006) in mothers and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 39 publications
(61 reference statements)
5
76
1
7
Order By: Relevance
“…These coping strategies for own pain might extend to how parents respond to child pain [18,22,28]. However, this is in contrast with evidence indicating that, in general, men have a bias toward problem-focused strategies relative to emotion-focused strategies [29,39].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These coping strategies for own pain might extend to how parents respond to child pain [18,22,28]. However, this is in contrast with evidence indicating that, in general, men have a bias toward problem-focused strategies relative to emotion-focused strategies [29,39].…”
Section: Discussionmentioning
confidence: 90%
“…Catastrophic thinking about one's child's pain has recently been discovered to be important in understanding parental responses [21,22]. Catastrophic thinking is the habitual misinterpretation of normal threat as awful and impossible to cope with [51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hermann et al, 2008;Huguet et al, 2008) may shed light on parental behaviours protecting the child from otherwise more negative outcomes (Vervoort et al, 2011b). It is likely that fathers, as compared to mothers, engage more often in the promotion of well-behaviours (Hechler et al, 2011) given their role in encouraging the child"s independence (Power and Shanks, 1989;Kenny and Gallagher, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that solicitous responses toward their children"s pain behaviour may increase sick-role behaviours and disability (Palermo and Eccleston, 2009), it is plausible that the association between parental catastrophizing and children"s disability may be explained by parents" solicitous behaviours. Previous findings indeed showed that catastrophizing (about own or child pain) is related with more solicitousness toward their child in pain (Langer et al, 2009;Hechler et al, 2011).…”
Section: Introductionmentioning
confidence: 92%